Government Size and Output Volatility : Should We Forsake Automatic Stabilization? - Pisani-Ferry, Jean (IMF Working Papers; Working Paper ;, 2008)
The paper takes stock of the debate on the positive link between output volatility and the size of government-which reflects automatic stabilizers. After a survey of the literature, we show that the contribution of automatic stabilizers to output stability may have disappeared since the 1990s. However, econometric analysis suggests that the breakdown in the government size-volatility relationship largely reflects temporary developments (better monetary management and financial intermediation). Once these factors are taken into account, the stabilizing role of government size remains important although little extra stability can be gained by expanding public expenditure beyond 40 percent of GDP.